Securitization of Migration and Human Rights in Europe - Topulli, Enela (European Journal of Multidisciplinary Studies, 2016)
The Post-Cold War period would face the states with new problems in the field of security. Among the most discussed and contested aspects of the respective agendas is the migration. The events of September 11th redefined the concept of security in line with the new non-state actors, that came into the system. Migration in this respect is perceived as associated with terrorism and as a threat to the security of states. The phenomenon is widely regarded as securitized. The question relates to the legitimacy of this process and to what extent it affects and impacts human rights and fundamental freedoms. It is widely recognized that there is a contradiction between the human rights framework and that of security. What is noted is the nature of the discrepancy and alternatives to manage the risks, that political elites see as inextricably linked to migration. The paper focuses on concrete cases, such as France, UK and EU.